1999
DOI: 10.1046/j.1365-2796.1999.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis and acute renal failure due to combination therapy with simvastatin and warfarin

Abstract: Abstract. Mogyoro Âsi A, Bradley B, Showalter A, Schubert ML (Medical College of Virginia/Virginia Commonwealth University and Hunter Holmes McGuire VAMC, Richmond, Virginia, USA). Rhabdomyolysis and acute renal failure due to combination therapy with simvastatin and warfarin (Case Report). J Intern Med 1999; 246: 599±602.Simvastatin, an inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, is widely used to treat hyperlipidaemia. Although myalgias are recognized adverse effects, clinically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Previous studies showed that a combination of simvastatin with fibrates, cyclosporine, digoxin, macrolide antibiotics, warfarin or azoles increased the risk of statin- mediated rhabdomyolysis [9,22,23]. Therefore, in our study, 10% of simvastatin users (4.3% of all statin users) are at a risk of developing rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous studies showed that a combination of simvastatin with fibrates, cyclosporine, digoxin, macrolide antibiotics, warfarin or azoles increased the risk of statin- mediated rhabdomyolysis [9,22,23]. Therefore, in our study, 10% of simvastatin users (4.3% of all statin users) are at a risk of developing rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 61%
“…Here, the cost of the medicines may have been the reason for the change – more expensive medicines were replaced with cheaper analogues without consideration of the potential risks due to drug interactions, which may become clinically significant, especially in the older population and in particular, in the case of polypharmacy [10, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the potentiating effect of warfarin on statin levels has not yet been studied in sufficient detail [79]. Pitavastatin and rosuvastatin are known to be weakly metabolized by CYP2C9 [80].…”
Section: Cyp2c9mentioning
confidence: 99%
“…Bisher wurden keine muskulären Nebenwirkungen, insbesondere keine CK-Erhöhung oder Rhabdomyolyse beschrieben [17,23,25]. [63], Diltiazem [65], Gemfibrozil [57,59], Mibefradil [72], Nefazodon [73], Pravastatin, Sildenefil [77], Troglitazone [78] oder Warfarin [79] Rhabdomyolysen beschrieben (Tabelle 3). Die Kombination Simvastatin mit Ezetimibe wurde von 40 Patienten ohne muskuläre Nebenwirkungen vertragen [8].…”
Section: Rosuvastatinunclassified